2019
DOI: 10.1021/acs.est.8b07254
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanofiber Membranes Incorporating PDMS-Aerogel Superhydrophobic Coating with Enhanced Flux and Improved Antiwettability in Membrane Distillation

Abstract: Electrospun nanofiber membranes (ENMs) have garnered increasing interest due to their controllable nanofiber structure and high void volume fraction properties in membrane distillation (MD). However, MD technology still faces limitations mainly due to low permeate flux and membrane wetting for feeds containing low surface tension compounds. Perfluorinated superhydrophobic membranes could be an alternative, but it has negative environmental impacts. Therefore, other low surface energy materials such as silica a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 52 publications
0
50
0
Order By: Relevance
“…Salvinia leaves) has directly influenced the choice of selected materials/chemicals and fabrication methods, which helped to improve the air retention ability. [142][143][144][145] (2) Controlling plastrons' environment: other methods attempt to work on the environmental conditions around the plastrons and how to make them less detrimental for plastrons' lifetime. In this case, the target is to record higher failure/ breakdown pressures than what would be achieved solely by optimising design/fabrication conditions.…”
Section: Approaches For Underwater Stability In Manufactured Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Salvinia leaves) has directly influenced the choice of selected materials/chemicals and fabrication methods, which helped to improve the air retention ability. [142][143][144][145] (2) Controlling plastrons' environment: other methods attempt to work on the environmental conditions around the plastrons and how to make them less detrimental for plastrons' lifetime. In this case, the target is to record higher failure/ breakdown pressures than what would be achieved solely by optimising design/fabrication conditions.…”
Section: Approaches For Underwater Stability In Manufactured Surfacesmentioning
confidence: 99%
“…More relevantly, re-entrant structures have been reported for water immersions and they were found to increase the breakdown pressure at which a Cassie-Wenzel transition takes place, making these surfaces more stable underwater compared to simple cylindrical textures. 145,161,162 Re-entrant structures are reported for the fabrication of distillation membranes, due to their stability against fluid pressures which enable their application under water-fluxes during the distillation process. 145,172,173 Lee et al reported a dual-layer membrane fabricated by; (1) electrospinning of polyvinylidene fluoride-cohexafluoropropylene (PVDF-HFP), followed by, (2) electrospraying of PVDF/PDMS-microspheres (Fig.…”
Section: Systems Inspired By Naturementioning
confidence: 99%
“…Deka et al [ 77 ] fabricated a brilliant superhydrophobic nanofiber composite membrane for MD application with a water contact angle of about 170°, high surface roughness, and high flux and stability for long-period operation (7 days), and an LEP of 129 kPa in very saline water by electrospraying of aerogel–PDMS solution on the PVDF–hexafluoropropylene electrospun nanofiber membrane. In addition, different types of SiO 2 nanoparticles were embedded in electrospun PVDF nanofiber membrane to add roughness and achieve superhydrophobic condition (contact angle > 150°) and narrow pore size distribution in the range of 1.2–1.4 µm.…”
Section: Applications Of Electrospun Nanofiber Compositesmentioning
confidence: 99%
“…In another work, Deka and coworkers [156] developed a novel electrospun membrane with high wetting resistance for MD-based desalination. In this study, the authors discussed that the perfluorinated membranes with superhydrophobic feature can be prepared and used as an alternative for seawater desalination.…”
Section: Electrospun Membranes For Thermally-driven Processesmentioning
confidence: 99%